Peran Dan Keterbatasan Bukti Digital Dalam Proses Peradilan Di International Criminal Court - Amanda Putri; Sania Ulfatun Nikmah; Naura Putri Ramadhania; Asep Suherman (GLOBAL SCIENTS PUBLISHER, 2026)
The development of information and communication technology has brought significant changes to the evidentiary system in international criminal law, particularly in the judicial process at the International Criminal Court. This study aims to analyze the role and limitations of digital evidence in supporting the process of proving international crimes, while also examining its implications for the principle of fair trial. The research method used is normative legal research with a statutory and conceptual approach, through a literature review of various relevant primary, secondary, and tertiary legal sources. The results show that digital evidence, such as video recordings, photographs, satellite imagery, and data from social media and open source intelligence (OSINT), plays a strategic role in uncovering facts, reconstructing events, and identifying perpetrators of international crimes, especially in conflict situations that are difficult to access directly. However, its use still faces various limitations, including those related to the validity, authenticity, and reliability of the evidence, and the lack of uniform international standards for its management. Furthermore, the complexity of digital evidence also poses challenges to the fulfillment of the principle of fair trial, particularly regarding the defendant's right to examine the evidence. Therefore, strengthening the legal framework, international standardization, and increasing technical capacity are necessary to ensure that the use of digital evidence supports the achievement of effective and integrated justice in the international criminal justice system.